Exclusive portfolio dealing and market inefficiency - Natalie Kessler; Iman van Lelyveld; Ellen van der Woerd (Tinbergen Institute, 2024)
We rationalize exclusive portfolio dealing in a novel three-period partial equilibrium framework populated by a representative, risk-neutral seller and a small number of ex ante identical broker-dealers. Endowed with independent, uncertain demand for a representative asset, the broker-dealers may compete in prices for exclusivity. If no exclusivity is granted, due to either the lack or seller rejection of offers, the seller enters a second-price auction with a zero-loss reserve price. While seller profits are constant under exclusivity (Bertrand Paradox), auction profits increase in the number of broker-dealers. Therefore, exclusivity arises in equilibrium only for a seller with at most two broker-dealers, reducing the trade frequency by one-third. The results are robust to endogenizing the number of broker-dealers and to allowing for the ex post asymmetry in asset demand. Exclusivity, however, does not arise when the auction features a seller-optimal reserve price. We motivate and conclude with an application to the security lending market.
Keywords: G14; G24; D43; D86; 330; Exclusive Dealing; Intermediated Markets; Competition; Market Efficiency